KARAKTERISASI ß-1,3-1,4-GLUKANASEBAKTERI ENDOFITIK Burkholderia cepacia ISOLATE76 ASAL TANAMAN PADI - Ifa Manzila; Tri Puji Priyatno; Muhammad Faris Fathin; Laksmi Ambarsari; Yadi Suryadi; I Made Samudera; Dwi Ningsih Susilowati (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Pathogenic fungus is one of the constraints to increase crop production. Chemical control using fungicides caused negative effects either to the environment or increased pathogen resistance to fungicide. Biological control using microbial-producing ß glucanase is an alternative method to inhibit the growth of pathogenic fungus. The aim of this study was to characterize ß-1,3-1,4-glucanase produced by rice endophytic bacterium, B. cepacia E76. Purification was carried out by ammonium sulphate precipitation, dialysis, and ion exchange chromatography using DEAE sepharose Fast Flow. A further characteristic of the enzyme activity was studied using oatmeal-glucan substrate.Results showed that precipitation using saturated 80% ammonium sulphate generated a good yield with the purity increased by 11 fold and yield of 66%.After chromatography step, the ß-1,3-1,4-glucanase of B. cepacia was successfully purified with an increasedof purity up to 33 fold and yield of 4%. Based on 10% SDS-PAGE, the enzyme profiles had the molecular weight of 15, 48 and 55 kDa.Of the three isozymes, only the 48 kDa isozyme showed the strongest glucanase activity when grown on media containing glucan as substrate.